2009
DOI: 10.1007/s10661-009-1114-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria with dual resistance to elevated concentrations of heavy metals and antibiotics in Nigerian contaminated systems

Abstract: Samples of soil, water, and sediments from industrial estates in Lagos were collected and analyzed for heavy metals and physicochemical composition. Bacteria that are resistant to elevated concentrations of metals (Cd(2+), Co(2+), Ni(2+), Cr(6+), and Hg(2+)) were isolated from the samples, and they were further screened for antibiotic sensitivity. The minimum tolerance concentrations (MTCs) of the isolates with dual resistance to the metals were determined. The physicochemistry of all the samples indicated wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 37 publications
3
36
0
6
Order By: Relevance
“…These results are Conc. (µl•ml −1 ) 100 300 100 300 100 300 100 300 100 300 100 300 100 300 in close agreement with findings of [25]. These metals are present in industrial effluents as in case of tannery solid waste.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are Conc. (µl•ml −1 ) 100 300 100 300 100 300 100 300 100 300 100 300 100 300 in close agreement with findings of [25]. These metals are present in industrial effluents as in case of tannery solid waste.…”
Section: Discussionsupporting
confidence: 84%
“…Xanthomonas maltophilia and Saprobic coryneform were studied by [10] from rhizosphere of wheat and barley. Previous work has revealed that potential bifenthrin degrading microorganisms were mostly Bacillus, Pseudomonas, Serratia, yeast and Fusarium [16] [21]- [25]. Present study revealed that both strains exhibited resistance to heavy metals were also resistant to antibiotics.…”
Section: Discussionmentioning
confidence: 54%
“…Intriguingly, Hg was the only HM to which all isolates were resistant. HM have been previously reported to potentially influence the selection process of antibioticresistant strains by affecting the means of survival, and if another resistance is present, shared mechanisms for both types of resistance are developed (Akinbowale et al 2007;Alonso et al 2000Alonso et al , 2001Baker-Austin et al 2006;Oyetibo et al 2009;Russell 2000). This process can lead to the dissemination of strains that are resistant to a vast number of antibiotics having a direct impact in human health, reducing the options for treatment and raising costs.…”
Section: Resultsmentioning
confidence: 99%
“…The isolation characterization and identification of the bacterial strains used in this study has been reported elsewhere (Oyetibo et al 2010). The bacterial strains w e r e P s e u d o m o n a s a e r u g i n o s a C A 2 0 7 N i , Burkholderia cepacia AL96Co, Corynebacterium kutscheri FL108Hg, and Rhodococcus sp.…”
Section: Microorganism and Culture Conditionsmentioning
confidence: 99%
“…Discharges of industrial wastewater into surrounding hydrosphere have been reportedly responsible for elevated concentrations of toxic metals in the receiving ecosystem (Oyetibo et al 2010;Oyeyiola et al 2006). HMs, as a notable environmental stressor, arouse or exacerbate environmental diseases, which often manifest as cancer, chronic lung disease, diabetes, and neuro-degeneration (Franco et al 2009;Hansen et al 2006;Valko et al 2005).…”
Section: Introductionmentioning
confidence: 99%